Strange structured elements in consumer's honey - Ortrud Monika Barth (Annals of Systems Biology - Peertechz Publications, 2022)
In order to obtain a better resolution of honey and bee pollen quality, it is essential to study them in nature, avoiding any chemical treatment. Besides pollen grains, trichomes, vegetable druses, mites, charcoal, fragments of plant tissues, amorphous brownish organic material, starch, finely granulate, dispersed gray vegetal material and oils are frequently detected. These elements interfere with the nutritional value of the products.